Myanmar : Requests for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Myanmar. (IMF Staff Country Reports; Country Report, 2021)
With the economy already slowing due to the COVID-19 pandemic in FY2019/20, a more intense second wave has hit Myanmar hard, inflicting large economic and social costs and straining the frail healthcare system. The needed strict lockdown measures have hurt manufacturing and spending further, while weak external demand has weighed on exports and tourism, though the kyat continued to appreciate as remittances remained robust. In FY2020/21, growth will decelerate further to 0.5 percent and open up external and fiscal financing gaps of about USD 1 billion. The IMF's RCF/RFI disbursement of 50 percent of quota (SDR 258.4 million) in June helped support the authorities' policy response for FY2019/20, particularly for social and health spending, kept monetary financing within target, and catalyzed financing from external partners, including through the Debt Service Suspension Initiative (DSSI).